Reconstructive breast surgery, assessment of patient’s satisfaction - Nowicki, Andrzej; Nikiel, Monika (Contemporary Oncology/Współczesna Onkologia, 2006)
Introduction: Breast reconstruction is an element of the complex treatment of breast cancer. A fundamental oncological contraindication is a confirmed generalisation of the disease, whereas resignation from the reconstruction procedure because of unfavourable prognostic factors is not necessary. Also, a complementary treatment, such chemotherapy or radiation, is not a contraindication factor. A decision made by a woman to undergo breast reconstruction should result from her own psychological motivation and should never be taken under the physician’s persuasion. The aim of this study was to examine the scope of patients’ functioning and their satisfaction with breast reconstruction surgery. Material and methods: 30 women were subjected to the surgery at the Chair and Clinic of Plastic Surgery and Scald Treatment at the Medical University of Gdansk in the period 2000-2003. The study was carried out among 20 patients via questionnaires sent by mail. The women’s age ranged from 22 to 63 years, while the average age was 48 years. Results: The largest group among the women who underwent surgery were patients within the age range 41-60, living in cities with their husband. Half of them have higher education degrees and good relationships with their families. The average time from breast amputation to reconstruction was 4.8 years. Most of the women did not feel rejected after the amputation. 70% of the women received understanding and support from the medical staff, while only 30% of them participated in the meetings of „Amazonka” clubs. A one-time correction of the second breast was done in 35% of the women during their breast reconstruction procedure. It appeared during the study that breast reconstruction after mastectomy brings the expected results in terms of patients” satisfaction. 75% of the women accept the appearance of their breasts after reconstruction treatment. Most of the women did not note any changes in the field of cultural-social life. In 75% of the women who underwent surgery their attractiveness improved in the opinion of their partners. A satisfaction level described as good or very good was observed in 75% of women. Conclusions: Our research shows that breast reconstruction after the amputation procedure produces the expected results in terms of patients” satisfaction. 75% of studied women accepted the appearance of their breast. About 60% of the patients did not see any effect of breast reconstruction on their intimate life. After breast reconstruction the women still fear metastasis and further deepening of the cancer disease.